Analisis Pengaruh Profitabilitas, Leverage, KSP dan KINS Terhadap Manajemen Laba (Earning Management) - Muliani Muliani; R . Ayu Ida Aryani (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2021)
Based on agency theory, earnings management occurs because of differences in economic interests between managers as agents and owners of companies as principals, where each party seeks to achieve the desired level of prosperity. Many factors affect both internal and external earnings management. This study aims to determine the effect of profitability, leverage, public share ownership (KSP) and institutional ownership (KINS) to earnings management (earning management).The sample in this research is the consumer goods industry sector listed on the BEI during the period 2013-2015. By using purposive sampling method, there are 42 companies that meet the criteria. Methods of data collection is done through documentation study and literature study. Data analysis techniques using descriptive statistical analysis, classical assumption test, and multiple linear regression analysis.The result of the research gives the conclusion that partially profitability, leverage, public share ownership and institutional ownership have no effect to earnings management. While simultaneously all independent variables have no effect on earnings management.